Reducing health inequities facing boys and young men of colour in the United States. (27th December 2020) - Smith, James A; Watkins, Daphne C; Griffith, Derek M
Summary: Health promotion research and practice consistently reveals that people of colour in the USA face multiple structural and systemic health and social inequities as a direct consequence of racism and discrimination. Recent scholarship on equity and men's health has highlighted the importance of gender—specifically concepts relating to masculinities and manhood—to better understand the inequities experienced by men of colour. A sharper focus on the intersection between race, gender and life stage has also emphasized the importance of early intervention when addressing inequities experienced by boys and young men of colour (BYMOC). This has led to an expansion of health promotion interventions targeting BYMOC across the USA over the past decade. Many of these health promotion strategies have attempted to reduce inequities through action on the social determinants of health, particularly those that intersect with education and justice systems. Reflecting on these developments, this commentary aims to discuss the challenges and opportunities faced by the health promotion community when attempting to reduce health and social inequities experienced by BYMOC. In doing so, the solutions we identify include: strengthening the evidence base about effective health promotion interventions; reducing system fragmentation; promoting connectivity through networks, alliances and partnerships; reducing tensions between collaboration and competition; changing the narrative associated with BYMOC; acknowledging both inclusiveness and diversity; addressing racism and intergenerational trauma; and committing to a national boys and men's health policy. We encourage health promotion researchers, practitioners and policy-makers to adopt these solutions for the benefit of BYMOC in the USA.